Regulating appetite in broilers for improving body and muscle development – A review. Issue 6 (26th June 2020) - te Pas, Marinus F. W.; Borg, Randy; Buddiger, Nico J. H.; Wood, Benjamin J.; Rebel, Johanna M. J.; van Krimpen, Marinus M.; Calus, Mario P. L.; Park, Jong‐Eun; Schokker, Dirkjan
Abstract: Appetite is the desire for feed and water and the voluntary intake of feed and is an important regulator of livestock productivity and animal health. Economic traits such as growth rate and muscle development (meat deposition) in broilers are directly correlated to appetite. Factors that may influence appetite include environmental factors, such as stress and temperature variation, and animal‐specific factors, such as learning period, eating capacity and preferences. Feed preferences have been reported to be determined in early life, and this period is important in broilers due to their fast growth and relatively short growth trajectories. This may be of importance when contemplating the use of more circular and sustainable feeds and the optimization of appetite for these feeds. The objective of this review was to review the biological mechanisms underlying appetite using data from human, animal and bird models and to consider the option for modulating appetite particularly as it relates to broiler chickens.